Analysis of the Competitiveness of Coastal Space Using Taxonomic Methods - Dariusz KLOSKOWSKI; Weronika KOSEK (Communications of International Proceedings, 2024)
Valorization of space in the investment aspect is the main direction of verification of areas that can be differentiated or show emerging poles of economic growth in the local, regional context, and even with an impact on the functioning of the country's economy. For this purpose, this study attempts to show the competitiveness of the seaside space and the impact of port functions on all changes in the environment, showing the determinants that differentiate municipal areas. The main aim of the study was to analyze the competitiveness of coastal communes on the Central Coast of Poland, which directly influence the valorization of coastal areas, including investment and tourism development. The selected research area, i.e. the South Baltic Sea of Poland, fits into the research topic, mainly due to the existence of high development potential of the maritime industry, which is not fully used. Additionally, the indicated area is a strategic element in the predictive approach of building a new transfer channel for goods to Southern European countries. The main subject of the study are coastal communes with an element of the sea port in Kołobrzeg, which is the basis for initiating a maritime cluster in this area, determining the development of Koszalin subregion and ultimately constituting an important nodal point on the map of Europe. Due to the limitations of literature related to the transformation of ports of similar importance to the port of Kołobrzeg, which could constitute an important pole of economic growth in the region with great potential in the future while inhibiting the tourist function, the following research methods were used: source data analysis, examination of documents and statistical data, as well as cause-and-effect analyses. In assessing the competitiveness of the seaside space, the taxonomic method of Hellwig's development measure was used, i.e. the non-standard development measure and Z. Hellwig's development pattern method. This method was used to examine a directly immeasurable phenomenon, which is competitiveness.
Keywords: port functions; competitiveness of towns; seaside space.